POPULIST NATIONALISM WHETHER ‘TRUMP’-ING THE LEGITIMACY IN THE CAUSE OF SOCIAL EQUALITY IN INTERNATIONAL LAW? - Thomas, Renjith; Jagani, Devi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The election of Trump marks the watershed in the history of International Law being an exemplification of a growing trend of populist nationalism globally, particularly after Brexit. Scholars recognize the predominant mode of articulation of these nationalist sentiments to be within the ‘cultural backlash’ theory. The authors explore the underlying legitimacy of the nationalist cause as being depicted by the concern of the economic have-nots over the unequal spread of the gains of globalization as having the potential to shatter the uncertain basis of international co-operation founded on trans-national economic integration. Deep tension ensues from this discrepancy between the non-progressive, retaliatory and state-centered claims of nationalism despite the legitimacy of the cause being universal. Such elitist articulation of a state’s interests/concerns in international law paves the way for a predominant use of the consensual theory to explain the scope of international co-operation, raising a problematic concern as to whether it is possible to by such distorted representation of the underlying legitimate claims of the people to trivialize the central liberal values, now universally accepted, as matters of mere politics and not governed by rules of law? Constitutionalism in international law is considered herein as an instrument to institutionalize the hierarchical superiority of certain liberal values and non-derogable core principles including the ideal of social equality as a basis of world peace. The researchers present this as one method to optimally reconcile the tensions in the present global order as it ultimately provides a framework to curtail the ability of those wielding the state’s political power to further the elitist agenda at the cost of the legitimate demand of the people, the ultimate beneficiaries of an international legal order. The paper emphasizes the urgent need to ease out these tensional elements, as realizing the goal of social equality is possible only by international co-operation.